HUMOR IN THE MOVIE “EVERYTHING EVERYWHERE ALL AT ONCE” USING VERBAL AND VISUAL ANALYSIS - Safitri, Nurlaila; Sulaiman, Iskandar; Sunra, La (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
This research discusses humor in the movie “Everything Everywhere All at Once” using verbal and visual analysis. It aims to analyze verbal and visual humor in the movie using the theory of Shade (1996) to analyze the types and the theory of Berger (2020) to identify the meaning of the verbal and visual humors found in the movie. The research method used in this study is qualitative descriptive method. The results of this research show that there are 12 extract describing verbal and visual humors found in the movie “Everything Everywhere All at Once”. There were 9 types of verbal humors found in the movie. They were jokes, pun, riddle, sarcasm, satire, parody, irony, farce, and wit. There were 3 types of visual humors that are character impersonation, practical jokes, and slapstick. It means that the movie do not fully contain the existing humor.